Perkembangan Kajian Ilmu Pemerintahan - Cornelis Lay; Wawan Mas'udi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Significant development colors the scope of study of politic and government. This ranges from the dynamic of government institutions and the formal government institutions to wider aspects of state, society and market including the relationships of these aspects. The following discusses the dorninant discourse of governance in political science and particularly in the study of government.